‘Responsiveness’ and ‘responsibility’: Determining what matters in a computer engineering curriculum - Winberg, Simon (South African Journal of Higher Education, 2016)
This paper is a research study related to the restructuring of a four-year BSc in Electrical and Computer Engineering (ECE) undergraduate degree programme. This paper focuses on the method by which collaborators from local industry and research institutions provided curriculum requests, and how these requests were organised and prioritised with the objective of defining knowledge that matters most to the degree programme. This study is part of an on-going department wide curriculum renewal process that started in 2009. Analysis of the data obtained led to development of a model to guide the curriculum project in identifying ways to prioritise changes that both protect the fundament disciplinary knowledge and cater for the dynamic nature of professional practice and changing technologies. This paper argues that two concepts, namely ‘responsiveness’ to the needs of industry and ‘responsibility’ to the disciplinary knowledge bases, are necessary aspects of an effective engineering curriculum.